Development and evaluation of aerogel-filled BMI sandwich panels for thermal barrier applications - Yong, Zhao (2018)
This study details a fabrication methodology envisaged to manufacture Glass/BMI honeycomb core aerogel-filled sandwich panels. Silica aerogel granules are used as core fillers to provide thermal insulation properties with little weight increase. Experimental heat transfer studies are conducted on these panels to study the temperature distribution between their two surfaces. Numerical studies are also carried out to validate the results. Despite exhibiting good thermal shielding capabilities, the Glass/BMI sandwich panels are found to oxidise at 180 ºC if exposed directly to heat. In order to increase the temperature bearing capacity and the operating temperature range for these panels, a way of coating them from outside with high temperature spray paint was tried. With a silicone-based coating, the temperature sustainability of these sandwich panels is found to increase to 350 ºC. This proved the effectiveness of the formed manufacturing process, selected high temperature coating, the coating method as well as the envisaged sandwich panel concept.